Financial, Non-Financial Information and the Performance of the Jordian Commercial Banks - Hussin, Mohmmad Anad (2011)
Profitability of commercial banks has been widely examined as a performance measure in developed countries but not in developing countries. This study measures the performance of commercial banks in Jordan by using ROA and ROE as profitability indicators affected by a group of financial factors (bank capital ratio, size and loans) and non-financial factors (market capitalization and trading volume) for the period 2005-2009. This study has shown that bank financial factors, which are capital and loans, have a negative and significant influence on profitability indicator ROE but not on ROA, while bank size has no significant impact on both bank profitability measures (ROA and ROE).Bank non-financial factor, market capitalization, has a negative and significant influence on ROA, while it has significant positive influence on ROE in Jordanian commercial banks for the period 2005-2009. Trading volume has strong significant and positive influence on both ROA and ROE. This suggests that trading volume can be considered as the determinant for the commercial banks’ profitability in Jordan for the period 2005-2009. The study also has concluded that the ROE has the superiority to ROA as profitability measure in testing the profitability of commercial banks in Jordan for the observed period.